2022
DOI: 10.3390/ijerph19159243
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cognitive Strategies Used by Cancer Patients as a Basis for Psychological Self-Support during Oncological Therapy

Abstract: Background: Cancer diagnosis is associated not only with health problems but also with psycho-social disability. Both medical and non-medical problems have impacts on cancer patients’ quality of life. The aim of the study was the identification of cognitive emotion regulation strategies among cancer patients during radiotherapy. Methods: The study was conducted on 78 radically treated cancer patients (median 63 years). A Cognitive Emotion Regulation Questionnaire (CERQ) was used. Results: Cancer patients mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Cognitive Emotion Regulation Questionnaire (CERQ), another focal point of the study, showed that cancer patients were more prone to self-blame, rumination, and catastrophizing, while demonstrating lower scores in adaptive strategies like positive refocusing and positive reappraisal. The inclination to catastrophize, coupled with tendencies for self-blame, can augment feelings of despair and powerlessness, further eroding their psychological well-being [11,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cognitive Emotion Regulation Questionnaire (CERQ), another focal point of the study, showed that cancer patients were more prone to self-blame, rumination, and catastrophizing, while demonstrating lower scores in adaptive strategies like positive refocusing and positive reappraisal. The inclination to catastrophize, coupled with tendencies for self-blame, can augment feelings of despair and powerlessness, further eroding their psychological well-being [11,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…While resilience, defined as the ability to "bounce back" and adapt amidst adversity, emerges as a pivotal construct [10], cognitive emotional regulation strategies-how individuals consciously manage and respond to emotionally laden situations-play an equally indispensable role. These strategies can range from re-appraisal and acceptance to suppression, guiding patients in processing and grappling with the intricate nuances of their diagnosis and treatment journey [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Further research has shown that patients living in urban areas were more likely to use putting into perspective and positive refocusing strategies than those in rural areas. 16 Age showed a negative association with refocusing on planning. 16 These findings indicate that cognitive emotion regulation strategies may vary among gender, residence, and age.…”
mentioning
confidence: 91%
“…People who smoke also often abuse alcohol [ 5 ]. Our previous study showed that lung cancer patients significantly most frequently used catastrophizing and rumination during oncological treatment [ 8 ]. Weiss et al [ 9 ] demonstrated that smoking was a significant predictor of personal stigmatization among patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%